Relationships of kin17 protein expression with clinical features and prognosis of colorectal cancer - Ruan, Liqin; Jiang, Qunguang; Zhang, Haitao (Translational Cancer Research; Vol 7, No 4 (August 31, 2018): Translational Cancer Research, 2018)
Background: To investigate the relationships of kin17 protein expression with the clinical features and prognosis of colorectal cancer (CRC). Methods: The clinicopathological data and paraffin specimens of 135 CRC patients in the First Affiliated Hospital of Nanchang University from November 2008 to November 2009 were collected. Immunohistochemistry was used to detect the kin17 protein expression in paraffin-embedded specimens, and the relationship between the kin17 protein expression and the clinicopathological features and prognosis of CRC were analyzed. Results: The kin17 protein expression was significantly higher in cancer tissue than in paracancerous tissue (49.6% vs. 14.8%, P